2010
DOI: 10.1186/1752-1947-4-84
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia farcinica lung infection in a patient with cystic fibrosis: a case report

Abstract: IntroductionRespiratory tract infections are the major causes of morbidity and mortality in patients with cystic fibrosis. Nocardia are rarely implicated in these infections and few reports of the involvement of this species are found in the literature.Case presentationWe describe a case of lung infection followed by chronic colonization of trimethoprim and sulfamethoxazole resistant Nocardia farcinica in a patient with cystic fibrosis. The chronic colonization of this uncommon bacterium in patients with cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…is opportunistic pathogens of immune compromised patients [9,10]. No source of infection could be detected in the current case as Nocardia are found in environment worldwide in fresh and salt water and soil type, dusts and fecal deposit of animal [11]. We report a case of pulmonary nocardiosis misdiagnosed initially as pulmonary tuberculosis because in most of the cases the chest radiogtraphy is pleomorphic and non-specific but consolidation and cavitary lesion are common [12,13], so the case was managed for along 15 months with anti T.B.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…is opportunistic pathogens of immune compromised patients [9,10]. No source of infection could be detected in the current case as Nocardia are found in environment worldwide in fresh and salt water and soil type, dusts and fecal deposit of animal [11]. We report a case of pulmonary nocardiosis misdiagnosed initially as pulmonary tuberculosis because in most of the cases the chest radiogtraphy is pleomorphic and non-specific but consolidation and cavitary lesion are common [12,13], so the case was managed for along 15 months with anti T.B.…”
Section: Discussionmentioning
confidence: 78%
“…In study published by Bittar et al [11] showed Nocardia farcinica in a 15 year old Caucasian boy with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, all isolates were susceptible to amikacin [10]. For patients with life-threatening infection, it seems prudent to initiate therapy with two or three drugs with the aim of switching to oral monotherapy when the patient's condition is stable and the results of in vitro studies are available [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy with imipenem and cefotaxime, amikacin and TMP/SMX, imipenem and TMP/SMX, amikacin and cefotaxime, or amikacin and imipenem was shown to be superior to single-agent therapy [11]. Some experts are of the opinion that combination of imipenem with amikacin should be started as the first-line therapy for cerebral and pulmonary nocardiosis [1].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a prolonged isolation of Nocardia in sputa must be taken into account and potentially treated despite stable clinical status. Finally, patients with particular clinical status (lung transplantation or strong immunosuppressive regimen or may be repeated corticoid treatment) must be treated because such conditions are known to induce nocardiosis [29].…”
Section: Discussionmentioning
confidence: 99%